Desensitization Protocol Administered Successfully With Interferon-? 2a in a Child With Chronic Hepatitis B Infection - Kilic, M.; Dogan, Y.; Taskin, E.; Sen, Y.; Kalpaklioglu, A. F. (Esmon Publicidad S A, Dept Allergy & Clin Immunol, Clin Univ Navarra, 2010)
[Abstract Not Available]
Keywords: Chronic Hepatitis B; Interferon-alpha; Children; Desensitization; Drug allergy